2022
DOI: 10.1088/1361-6668/ac56ff
|View full text |Cite
|
Sign up to set email alerts
|

Normal zone propagation in various REBCO tape architectures

Abstract: The normal zone propagation velocity (NZPV) of three families of REBCO tape architectures designed for superconducting fault current limiters (SFCLs) and to be used in high voltage direct current (HVDC) transmission systems has been measured experimentally in liquid nitrogen at atmospheric pressure. The measured NZPVs span more than three orders of magnitude depending on the tape architectures. Numerical simulations based on finite elements allowed to reproduce well the experiments. The dynamic current transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…Furthermore, the rise of the electric field is approximately 60 V m −1 s −1 which is 50 times higher than the pristine sample. This is consistent with NZPV measurements performed on theses samples, where it was found that the bCFD-sulfide sample had a NZPV 18 times higher than the pristine sample [15].…”
Section: Current Limitation Testssupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, the rise of the electric field is approximately 60 V m −1 s −1 which is 50 times higher than the pristine sample. This is consistent with NZPV measurements performed on theses samples, where it was found that the bCFD-sulfide sample had a NZPV 18 times higher than the pristine sample [15].…”
Section: Current Limitation Testssupporting
confidence: 90%
“…However, in our experimental setup, we reached the objective of partially sulfurized the silver without degrading the superconductor by exposing a tape for 3.5 h to the sulfur gas. Moreover, the expected quench performance associated with NZPV boost coming from the bCFD architecture previously demonstrated [15] was confirmed by DC limitation tests. The tests revealed that the voltage raised much faster with the bCFD-sulfide sample (60 V s −1 ) in comparison with the pristine sample (1.2 V s −1 ).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Other strategies have been investigated by ICMAB during FASTGRID. The last and most promising is based on a silver sulfide insulating layer [20], whose industrial implementation is rather easy. This time, the CFD effect was clearly experimentally demonstrated.…”
Section: Cfd Implementationmentioning
confidence: 99%